2002
DOI: 10.1074/jbc.m200468200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C and ERK Activation Are Required for TFF- peptide-stimulated Bronchial Epithelial Cell Migration and Tumor Necrosis Factor-α-induced Interleukin-6 (IL-6) and IL-8 Secretion

Abstract: TFF-peptides (formerly P-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 65 publications
7
70
1
Order By: Relevance
“…Also, the tumor cells inside the metastatic lymph nodes of the TFF2-positive patients were strongly positive for TFF2, indicating that TFF2-positive cell lineage metastasized to the regional lymph nodes and the metastatic phenotype could be attributable to the TFF2 expression by the tumor cells. This finding further strengthens the conclusions of previous in vitro studies stating that TFF2 is intricately related with cancer cell motility and invasion (Efstathiou et al, 1999;Emami et al, 2001;Graness et al, 2002;Playford et al, 1995). In an in vitro wound-induced cell migration assay using confluent rat intestinal epithelial cells, Dignass et al (1994) showed that application of TFF2 enhanced migration of cells into the wound approximately 4-fold.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Also, the tumor cells inside the metastatic lymph nodes of the TFF2-positive patients were strongly positive for TFF2, indicating that TFF2-positive cell lineage metastasized to the regional lymph nodes and the metastatic phenotype could be attributable to the TFF2 expression by the tumor cells. This finding further strengthens the conclusions of previous in vitro studies stating that TFF2 is intricately related with cancer cell motility and invasion (Efstathiou et al, 1999;Emami et al, 2001;Graness et al, 2002;Playford et al, 1995). In an in vitro wound-induced cell migration assay using confluent rat intestinal epithelial cells, Dignass et al (1994) showed that application of TFF2 enhanced migration of cells into the wound approximately 4-fold.…”
Section: Discussionsupporting
confidence: 76%
“…However, it is possible that TFF2 might contribute to tumor progression in other ways, such as cell migration, angiogenesis, or immune suppression. Indeed, several studies have supported a role with respect to cell migration and possibly invasion (Efstathiou et al, 1999;Emami et al, 2001;Graness et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Human intestinal trefoil factor (TFF3, gene symbol hITF) is a member of a family of polypeptides characterized by containing at least one copy of the trefoil motif, a 3-leaved structure formed by three conserved disulfides within a 40-amino acid segment [1,2]. Trefoil peptides are expressed mainly in gastrointestinal and other selected epithelial tissues and are packaged along with mucins and secreted [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental induction of ulceration in the rat stomach leads to rapid up-regulation of TFF2 expression with high levels observed 30 min after ulceration with persistence for up to 10 days (1). TFF2 is secreted into the mucus layer of the gastrointestinal tract of mammals where it stabilizes the mucin gel layer and stimulates migration of epithelial cells (2)(3)(4), suggesting an important role in restitution and in maintenance of the integrity of the gut. Exogenous administration of recombinant TFF2, either orally or intravenously, provides mucosal protection in several rodent models of acute gastric or intestinal injury (5,6).…”
mentioning
confidence: 99%